Lens thickness and associated factors - Jonas, Jost B. (Clinical & experimental ophthalmology, 2012)
Background: To determine the normative data for lens thickness and its associated factors in a population-based study. Design: Population-based study. Participants: The Central India Eye and Medical Study included 4711 subjects (aged 30+ years). Methods: The subjects underwent a detailed ophthalmological examination including measurement of the lens thickness by sonography. Main Outcome Measure: Sonographic lens thickness measurement. Results: After excluding pseudophakic or aphakic eyes, lens thickness measurements were available for 9046 eyes of 4610 (97.9%) subjects with a mean age of 49.1 ± 13.2 years (range: 30-100 years) and a mean refractive error of −0.11 ± 1.77 dioptres (median, 0 dioptres; range, −21.75 to +7.75 dioptres). Mean lens thickness was 3.95 ± 0.49 mm. In multivariate analysis, a thick lens was significantly associated with higher age (P < 0.001), male gender (P < 0.001), higher body stature (P = 0.02), higher body mass index (P = 0.003), thicker central cornea (P = 0.008), shallower anterior chamber depth (P < 0.001) and hyperopic refractive error (P < 0.001). After adjustment for ocular and systemic parameters, lens thickness decreased with higher degree of nuclear cataract. Conclusions: In the rural Central Indian population, a thick lens was associated with higher age, male gender, high body stature, high body mass index, hyperopia, thick central cornea, shallow anterior chamber depth and nuclear cataract. The data may be helpful to explain anatomic relationships of the anterior segment of the eye and to elucidate risk factors of diseases associated with ocular dimensions.